2001
DOI: 10.1007/s00586-001-0365-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative three-dimensional anatomy of lumbar vertebrae in Singaporean Asians

Abstract: This paper details the quantitative three-dimensional anatomy of lumbar vertebrae L1-L5 from Asian (Singaporean) subjects based on 60 lumbar vertebrae from 12 cadavers. The purpose of the study was to measure the dimensions of the various parameters of the lumbar vertebrae and thereafter to compare the data with a study performed on Caucasian specimens. Measurements were taken with the aid of a three-dimensional digitiser. The means and standard errors for linear, angular and area dimensions of the vertebral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 7 publications
1
27
1
1
Order By: Relevance
“…17 Studying the diameter and morphology of pedicle is important in several fields including better knowledge of the anatomy 1,6,7,11,18,19 and pedicle orientation, 1,3 which are essential to minimize neurologic complications. In addition, these studies help to better understand the spinal kinematics and mechanisms of injury to the spinal column, 8 which provide important data for the designers of these instruments and guide surgeons who use the instruments. 10,17 In the lumbar area, detailed anatomical knowledge is critical for performing a safe operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Studying the diameter and morphology of pedicle is important in several fields including better knowledge of the anatomy 1,6,7,11,18,19 and pedicle orientation, 1,3 which are essential to minimize neurologic complications. In addition, these studies help to better understand the spinal kinematics and mechanisms of injury to the spinal column, 8 which provide important data for the designers of these instruments and guide surgeons who use the instruments. 10,17 In the lumbar area, detailed anatomical knowledge is critical for performing a safe operation.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] These data also provide the anatomy of the vertebral column with the necessary information to assess the pedicles. [8][9][10] It is believed that race has an impact on the physical properties of lumbar vertebral column including mean canal diameters, the size of vertebral body, morphometry, and the size of the pedicles. 9,11 It is also different among different populations.…”
mentioning
confidence: 99%
“…There are only a few studies which regard the quantitative anatomy of the lumbar SP (18, 19). In our study, we had similar findings with reported studies which claimed that L3 had the longest SP in most of the patients from the study groups.…”
Section: Discussionmentioning
confidence: 99%
“…The same specimen was also used in the morphology study conducted by Tan et al 16 and found to be in approximately 50 th percentile of the samples. The cadaver was inspected to be free from spinal disease, metastasis and trauma.…”
Section: Methodsmentioning
confidence: 99%